Mix and print: fast optimization of mesoporous CuCeZrOw for catalytic oxidation of n-hexane1. Issue 38 (11th May 2015) - Huang, Fenfen; Wang, Shenliang; Yi, Wuzhong; Zou, Shihui; Chen, Changlei; Xiao, Liping; Liu, Xiaonao; Fan, Jie
<x xml:space="preserve">Abstract</x> Fast optimization of mesoporous ternary metal oxide (CuCeZrOw) catalysts for n-hexane oxidation is achieved via a newly developed combinatorial approach based on ink-jet printing assisted synthesis and multi-dimensional group testing.